The Effects of Using Gamification and Cooperative Learning with the Team Games Tournament (TGT) Method for Prathom Sueksa Six Students - Jueajarn, Porntana; Insaard, Sayamon; Ingard, Supot (ECT Education and Communication Technology Journal, 2025)
This quasi-experimental research aimed to (1) develop gamification with cooperative learning using the Team Games Tournament (TGT) method for Prathom Sueksa Six students, (2) examine the effects of using this approach, and (3) investigate student satisfaction with the gamification and TGT cooperative learning method. The sample population consisted of thirty Prathom Sueksa Six students in one classroom at Assumption Samut Prakan School during the first semester of the academic year 2024, selected using simple random sampling by drawing lots. The research instruments included: 1) a lesson plan using gamification with cooperative learning through the TGT method, 2) gamification with cooperative learning through the TGT method, 3) a gamification media quality assessment form, 4) a programming skills assessment form, and 5) a satisfaction questionnaire. Data were analyzed using mean and standard deviation. The findings were as follows: 1) The developed gamification with cooperative learning using the TGT method for Prathom Sueksa Six students showed very good content quality (M = 4.77, SD = 0.19) and very good media quality (M = 4.53, SD = 0.18). 2) Students demonstrated very good programming ability when using gamification with cooperative learning through the TGT method, with an overall mean score 32.60. 3) Student satisfaction with the gamification and cooperative learning using the TGT method was at the highest level (M = 4.87, SD = 0.07).